Curable composition

The urea (meth)acrylate produced by reacting organic polyisocyanate with a specific structure and (meth)acrylate, solves the color change and hardness flexibility balance of the active linear hardening composition when increasing the curing speed, and realizes efficient and environmentally friendly hardened film application.

JP2025015076APending Publication Date: 2025-01-30TOAGOSEI CO LTD

Patent Information

Application Number
JP2023118181
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

In the prior art, active-performance linear hardening compositions tend to cause color changes and elasticity reduction when increasing the curing speed, and the content of metal oxides limits its application in electronic materials and insulating materials, and the hardening film depth is insufficient, making it difficult to balance hardness and flexibility.

Method used

Urea (meth)acrylate produced by reacting organic polyisocyanate with a specific structure and (meth)acrylate, through the active linear hardening composition, it contains a specific proportion of photopolymerization initiator and other additives, ensuring the high hardness and flexibility of the hardened film.

Benefits of technology

While achieving efficient curing in a short time, the hardened film has excellent hardness and flexibility, suitable for electronic materials and insulating materials, reducing environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015076000001
    Figure 2025015076000001
  • Figure 2025015076000002
    Figure 2025015076000002
Patent Text Reader

Abstract

To provide a curable composition excellent in curability and capable of achieving both hardness and flexibility of a cured coating film obtained therefrom.SOLUTION: The curable composition contains the following component (A): a reaction product of an organic polyisocyanate (a1) having an odd number of methylene group structures and at least one (meth)acrylate (a2) having one or more hydroxyl groups and an acrylic equivalent of 50-200 g / eq.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a curable composition containing a urethane (meth)acrylate having a (meth)acryloyl group (hereinafter referred to as "urethane (meth)acrylate"), and preferably to an active energy ray-curable composition. The composition of the present disclosure can be used for various applications, and in particular, it has faster curing properties than conventional urethane (meth)acrylates, and the cured film has excellent hardness and flexibility. Therefore, it can be preferably used for applications such as inks, coating agents, adhesives, etc., and belongs to these technical fields. [Background technology]

[0002] Active energy ray-curable compositions can be cured by exposure to active energy rays such as ultraviolet rays, visible light, and electron beams for a very short time, and are industrially used in a wide range of applications as inks and coating agents for various equipment and materials due to their high productivity. In addition, active energy ray-curable compositions do not contain solvents such as water and organic solvents, so they do not require a process for removing the solvent. They can reduce energy costs and do not require solvents, so they have been attracting attention in recent years from the perspective of reducing environmental impact.

[0003] Furthermore, the curing of the active energy ray curable composition occurs by free radical polymerization of monomers and oligomers having ethylenically unsaturated groups present in the active energy ray curable composition. When a composition containing a photoinitiator is irradiated with a reaction initiation dose of active energy rays, radicals are generated from the photoinitiator, and a radical polymerization reaction is initiated. The active energy rays can be emitted by a source of actinic radiation such as UV light, and can be provided by visible light such as high or medium voltage mercury bulbs, xenon bulbs, carbon arc lamps, metal halide bulbs, LED light sources (i.e., UV-LED lamps), and / or sunlight.

[0004] If the amount of photoinitiator added is increased in order to improve the curability of the active energy ray-curable composition, there is a risk that the remaining photoinitiator will change the color tone or elastic modulus of the cured film over time, that the reacted photoinitiator will bleed onto the surface of the cured coating film, causing a deterioration in the appearance, and further that the curability of the deeper part of the cured coating film will be insufficient, making it impossible to obtain the desired performance in various applications such as paints and inks. Therefore, it is not appropriate to adopt a measure of increasing the amount of photoinitiator added in order to promote curing.

[0005] For example, Patent Document 1 discloses a method for accelerating curing by using a composition containing a small amount of a photoinitiator and a metal oxide, where the metal oxide is available to support additional radical reactions without undergoing irreversible chemical changes.

[0006] For example, Patent Document 2 discloses a urethane (meth)acrylate resin composition that is composed of a specific isocyanate compound and a dipentaerythritol (meth)acrylate having a specific hydroxyl value, and that can provide a coating film that is excellent in abrasion resistance, flexibility, curl resistance, and impact resistance. Furthermore, Patent Document 3 discloses a curable composition that contains DPHA as a main component and provides a cured coating film with excellent hardness. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 2022-60346 [Patent Document 2] Patent application 2019-560932 [Patent Document 3] Patent Publication No. 2023-49953 Summary of the Invention [Problem to be solved by the invention]

[0008] However, since the composition described in Patent Document 1 contains a metal oxide, it is restricted in that it cannot be used in applications where metals have a detrimental effect on performance, such as in the fields of electronic materials and insulating materials.

[0009] Moreover, there is no mention of a urethane (meth)acrylate resin composition having excellent curability in Patent Document 2. Furthermore, the reason why the hardness of the cured coating film of the composition described in Patent Document 3 is excellent is because the composition becomes a glassy state at a low reaction rate, and therefore there is a problem in that it is difficult to increase the reaction rate.

[0010] An object of the present disclosure is to provide a curable composition that has excellent curability and can provide a cured coating film that has both high hardness and flexibility. [Means for solving the problem]

[0011] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that a curable composition containing a urethane (meth)acrylate obtained by a urethanization reaction between an organic polyisocyanate having a specific structure and a specific (meth)acrylate has excellent curability, and the cured film produced thereby has excellent hardness and flexibility, and have completed the present disclosure. Means for solving the above problems include the following aspects. <1> A curable composition comprising the following component (A): Component (A): A reaction product of an organic polyisocyanate (a1) having an odd number of methylene group structures and at least one (meth)acrylate (a2) having one or more hydroxyl groups and an acrylic equivalent of 50 to 200 g / eq. <2> The organic polyisocyanate (a1) is a polyisocyanate having a pentamethylene group. <1> The curable composition according to claim 1. <3> The (meth)acrylate (a2) is a (meth)acrylate obtained by reacting one alcohol selected from the group consisting of polyhydric alcohols having 3 to 6 hydroxyl groups with a compound having one (meth)acryloyl group. <1> or <2> The curable composition according to claim 1. <4> It is an active energy ray curing type. <1> ~ <3> 13. The curable composition according to claim 12, <5> The composition contains 0.1 to 10 parts by mass of a photopolymerization initiator for 100 parts by mass of a component having an ethylenically unsaturated bond, is coated to a thickness of 10 μm, and has a UV-A intensity of 250 mW / cm 2 , 200mJ / cm 2 and a mass (C2) of the cured film obtained by immersing the cured film in ethyl acetate, leaving the cured film at rest for 24 hours in a 25°C environment, filtering the cured film using a 200-mesh filter cloth, and drying the cured film. The gel fraction calculated by the following formula (X) is 95% or more. <1> ~ <4> 13. The curable composition according to claim 12, Gel fraction = C2 / C1 × 100 (X) C1: Mass of the cured film before immersion in ethyl acetate C2: Mass of the cured film after immersion in ethyl acetate <6> The component (A) accounts for 60 mass% or more of the ethylenically unsaturated bond-containing component (100 mass%). <5> The curable composition according to claim 1. <7> For coating agents, <1> ~ <6> 13. The curable composition according to claim 12, The present disclosure will be described in detail below. Effect of the Invention

[0012] The composition of the present disclosure has excellent curability, and the cured film has excellent hardness and flexibility. Therefore, the composition of the present disclosure can be preferably used for applications such as inks, coating agents, and adhesives. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In this disclosure, "monofunctional" means a compound having one ethylenically unsaturated group, "bifunctional" means a compound having two ethylenically unsaturated groups, and "polyfunctional" means a compound having three or more ethylenically unsaturated groups. In the present disclosure, acryloyl groups and / or methacryloyl groups are referred to as (meth)acryloyl groups, acrylates and / or methacrylates are referred to as (meth)acrylates, and acrylic acid and / or methacrylic acid are referred to as (meth)acrylic acid.

[0014] The present disclosure relates to a curable composition comprising the following component (A): Component (A): A reaction product of an organic polyisocyanate (a1) having an odd number of methylene group structures and at least one (meth)acrylate (a2) having one or more hydroxyl groups and an acrylic equivalent of 50 to 200 g / eq. The curable composition comprising component (A), its method of use, and applications will be described below.

[0015] 1. Component (A) The component (A) of the present disclosure is a reaction product of an organic polyisocyanate (a1) having an odd number of methylene group structures and at least one (meth)acrylate (a2) having one or more hydroxyl groups and an acrylic equivalent of 50 to 300 g / eq. The methods for producing the organic polyisocyanate (a1), the (meth)acrylate (a2), and the component (A) will be described below.

[0016] 1-1. Organic polyisocyanate (a1) The organic polyisocyanate (a1) has an odd number of methylene group structures. The organic polyisocyanate (a1) preferably has an odd number and a multiple of 5 of methylene group structures, and more preferably has 5 or 15 methylene group structures. The organic polyisocyanate (a1) includes aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates. As the organic polyisocyanate (a1), aliphatic polyisocyanates and alicyclic polyisocyanates are preferred because they are excellent in light resistance, i.e., the coating film obtained by curing the curable composition is less likely to yellow, and further, even when the cured coating film is used for applications such as coating for a long period of time, the coating film is less likely to become discolored over time. As the organic polyisocyanate (a1), aliphatic polyisocyanates are more preferred since the resulting urethane (meth)acrylate is less likely to yellow, and pentamethylene diisocyanate and isocyanurates of pentamethylene diisocyanate are particularly preferred because of their excellent curing properties.

[0017] 1-2. (Meth)acrylate (a2) The (meth)acrylate (a2) is at least one kind of (meth)acrylate having one or more hydroxyl groups and an acrylic equivalent of 50 to 200 g / eq.

[0018] As the (meth)acrylate (a2), a (meth)acrylate obtained by reacting one kind of alcohol selected from the group consisting of polyhydric alcohols having 3 to 6 hydroxyl groups with a compound having one (meth)acryloyl group is preferred in terms of excellent reactivity with the organic polyisocyanate (a1).

[0019] The (meth)acrylate (a2) can be obtained, for example, by transesterification of a monofunctional (meth)acrylate with one alcohol selected from the group consisting of polyhydric alcohols having 3 to 6 hydroxyl groups. The (meth)acrylate (a2) can also be obtained, for example, by dehydration esterification of a polyhydric alcohol having 3 to 6 hydroxyl groups with (meth)acrylic acid.

[0020] The acrylic equivalent of the (meth)acrylate (a2) is from 50 to 200 g / eq, preferably from 70 to 160 g / eq, and more preferably from 80 to 120 g / eq. When the (meth)acrylate (a2) has an acrylic equivalent of 50 g / eq or more, it is possible to improve the strength of the cured film of the composition containing the (A) component obtained. When the acrylic equivalent is 200 g / eq or less, it is possible to improve the water resistance of the cured film. In the present disclosure, the acrylic equivalent means a value measured in accordance with the method defined in JIS K 2605-1996.

[0021] Specific examples of polyhydric alcohols having 3 to 6 hydroxyl groups include polyglycerols such as glycerin, diglycerin, and tetraglycerin, sorbitol, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, tri(2-hydroxyethyl)isocyanurate, and alkylene oxide adducts of these polyhydric alcohols. In this case, examples of the alkylene oxide in the alkylene oxide adduct include ethylene oxide, propylene oxide, tetramethylene oxide, polyethylene oxide, and polypropylene oxide.

[0022] Specific examples of the (meth)acrylate (a2) include glycerin mono(meth)acrylate, glycerin di(meth)acrylate, glycerin tri(meth)acrylate, diglycerin mono(meth)acrylate, diglycerin di(meth)acrylate, diglycerin tri(meth)acrylate, diglycerin tetra(meth)acrylate, tetraglycerin mono(meth)acrylate, tetraglycerin di(meth)acrylate, tetraglycerin tri(meth)acrylate, tetraglycerin tetra ... Laglycerin penta(meth)acrylate, tetraglycerin hexa(meth)acrylate, sorbitol mono(meth)acrylate, sorbitol di(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tetra(meth)acrylate, sorbitol penta(meth)acrylate, sorbitol hexa(meth)acrylate, pentaerythritol mono(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate tetra(meth)acrylate, dipentaerythritol mono(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane mono(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane Examples of the alkylene oxide adducts include di(meth)acrylate, ditrimethylolpropane mono(meth)acrylate, ditrimethylolpropane di(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and alkylene oxide adducts of these (meth)acrylates, mono(meth)acrylates of alkylene oxide adducts of isocyanuric acid, di(meth)acrylates of alkylene oxide adducts of isocyanuric acid, tri(meth)acrylates of alkylene oxide adducts of isocyanuric acid, etc. Also, those using alcohols of different structures as raw materials may be used in combination.

[0023] As the (meth)acrylate (a2), those obtained by various production methods can be used. For example, there can be mentioned those obtained by the transesterification reaction of a polyhydric alcohol with a monofunctional (meth)acrylate in the presence of an ester exchange catalyst, or those obtained by the dehydration esterification of a polyhydric alcohol with (meth)acrylic acid in the presence of an acidic catalyst.

[0024] Of the above-mentioned production methods, the (meth)acrylate (a2) obtained by transesterification is preferred because it contains fewer impurities and can give the desired (meth)acrylate.

[0025] 1-3.Polyol The component (A) of the present disclosure may further contain a polyol in addition to the organic polyisocyanate (a1) and the (meth)acrylate (a2). Examples of the polyol include low molecular weight diols, polyether polyols, polycarbonate polyols, polyester polyols, and diols having a polyene skeleton.

[0026] Examples of low molecular weight diols include ethylene glycol, propylene glycol, butanediol, 1,6-hexanediol, 2-methyl-1,8-octanediol, nonanediol, cyclohexanedimethanol, neopentyl glycol, 3-methyl-1,5-pentanediol, and hydroxypivalic acid neopentyl glycol ester.

[0027] The polyether polyol may be a polyalkylene glycol having two or more oxyalkylene units, such as polyoxyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0028] Polycarbonate polyols include reaction products of carbonates with the low molecular weight diols described above, such as diaryl carbonates, such as diphenyl carbonate, and dialkyl carbonates, such as dimethyl carbonate and diethyl carbonate.

[0029] The polyester polyol may be a reaction product of at least one selected from the group consisting of the low molecular weight diol, polyether polyol, and polycarbonate polyol, with an acid component. Examples of the reaction product include dibasic acids such as adipic acid, sebacic acid, succinic acid, maleic acid, phthalic acid, hexahydrophthalic acid, and terephthalic acid, or anhydrides thereof, and ring-opening reaction products of polycarbonate diol and caprolactone.

[0030] 1-4. Manufacturing method of component (A) The component (A) can be produced by heating and stirring the organic polyisocyanate (a1) and the (meth)acrylate (a2) in the presence of a polyol, a catalyst, and a solvent as necessary to form a urethane. In this case, the organic polyisocyanate (a1) and the (meth)acrylate (a2) can be charged all at once and reacted (hereinafter referred to as a one-step reaction). In the presence of a polyol, a one-step reaction or the organic polyisocyanate (a1) and the polyol can be reacted first, and then the (meth)acrylate (a2) can be added (hereinafter referred to as a two-step reaction). In the presence of a polyol, the reaction liquid becomes highly viscous during the urethane reaction, making the reaction difficult, so it is preferable to produce the component by a two-step reaction.

[0031] In the urethanization reaction, various catalysts are known, and any of them can be used to efficiently advance the urethanization reaction in a short period of time. Specific examples of the catalyst include tin compounds such as dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctate, and dibutyltin diacetylacetonate; bismuth compounds such as bismuth dioctate; iron compounds such as iron acetylacetonate; zinc compounds such as zinc acetylacetonate; and amine compounds such as triethylamine. The above catalysts may be used alone or in combination of two or more.

[0032] The amount of the catalyst to be added may be a catalytic amount, and is preferably 0.01 to 1,000 wtppm, more preferably 0.1 to 1,000 wtppm, relative to the reaction solution. By setting the amount of the catalyst to 0.01 wtppm or more, the urethane reaction can be favorably advanced, and by setting the amount to 1,000 wtppm or less, coloration of the obtained (A) component can be suppressed.

[0033] The catalyst is preferably added when the organic polyisocyanate (a1) and the (meth)acrylate (a2) are charged.

[0034] If the molecular weight of the component (A) produced by this reaction becomes high, the reaction mixture becomes highly viscous and may become difficult to stir. For this reason, a solvent may be added to the reaction components. The solvent is preferably one that is not involved in the urethanization reaction, and examples of the solvent include organic solvents such as aromatic solvents such as toluene and xylene, ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone, ether solvents such as diethyl ether and tetrahydrofuran, and ester solvents such as ethyl acetate and butyl acetate. When an organic solvent is used, its amount can be appropriately determined depending on the viscosity of the resulting component (A) and other factors, but is preferably set so that its amount in the reaction solution is 0 to 70% by mass. Here, the reaction solution means the total amount of the raw material compounds when only the raw material compounds are used, and means the total amount including the reaction solvent and the like when the raw material compounds are used in addition to the reaction solvent and the like. Specifically, it means a solution of the organic polyisocyanate (a1), the (meth)acrylate (a2), and the polyol, catalyst, solvent, polymerization inhibitor, and the like used as necessary.

[0035] In the urethanization reaction, it is preferable to use a polymerization inhibitor to prevent polymerization of the (meth)acryloyl group of the raw material or the product, and further, an oxygen-containing gas may be introduced into the reaction liquid. Examples of the oxygen-containing gas include air and a mixed gas of oxygen and nitrogen. Polymerization inhibitors include organic polymerization inhibitors, inorganic polymerization inhibitors, and organic salt polymerization inhibitors. Examples of organic polymerization inhibitors include phenolic compounds such as hydroquinone, tert-butylhydroquinone, hydroquinone monomethyl ether, 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tri-tert-butylphenol, and 4-tert-butylcatechol, quinone compounds such as benzoquinone, stable radicals such as galvinoxyl, 2,2,6,6-tetramethylpiperidine-1-oxyl, and 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, phenothiazine, and ammonium N-nitroso-N-phenylhydroxylamine. Examples of inorganic polymerization inhibitors include copper chloride, copper sulfate, and iron sulfate. Examples of organic salt polymerization inhibitors include nitroso compounds such as aluminum salt of N-nitroso-N-phenylhydroxylamine and ammonium N-nitrosophenylhydroxylamine, and copper dibutyldithiocarbamate. These can be used alone or in combination of two or more types. The proportion of the polymerization inhibitor in the reaction liquid is preferably 5 to 20,000 wtppm, and more preferably 25 to 3,000 wtppm.

[0036] The reaction temperature may be appropriately set depending on the raw materials used and the structure and molecular weight of the desired component (A), but is usually preferably 25 to 150°C, more preferably 30 to 120°C. By setting the reaction temperature at 25°C or higher, the reaction rate can be increased, and by setting the reaction temperature at 150°C or lower, thermal polymerization of the (meth)acryloyl group in the raw materials or product can be suppressed, or coloring of the reaction liquid can be suppressed, and the purification step after the reaction can be simplified. The reaction time may be appropriately set depending on the raw materials used and the structure and molecular weight of the desired component (A).

[0037] In the present disclosure, the viscosity of component (A) is preferably 100 to 50,000 mPa·s, more preferably 300 to 30,000 mPa·s, and even more preferably 500 to 10,000 mPa·s at 50° C., from the viewpoint of improving the coatability of the composition and the strength of the coating film. Note that in the present disclosure, the viscosity refers to the value measured at 50° C. using an E-type viscometer (cone-plate type viscometer).

[0038] From the viewpoint of improving the coatability and adhesion to a substrate, the content of component (A) in the composition of the present disclosure is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, relative to 100% by mass of the composition of the present disclosure.

[0039] 2.Curing composition The present disclosure relates to a curable composition containing the component (A). The composition may be produced by a conventional method, for example by stirring and mixing component (A) and, if necessary, other components. The stirring condition and stirring time can be determined by visually checking that the composition is in a homogeneous state, and the conditions can be appropriately adjusted depending on the state. In this case, heating may be performed as necessary. The heating temperature may be appropriately set depending on the components contained in the composition used, the substrate to be coated with the composition, the purpose of use, etc., but is preferably room temperature to 80°C.

[0040] The composition of the present disclosure can be used as an active energy ray-curable composition or a heat-curable composition, and is preferably used as an active energy ray-curable composition.

[0041] The composition of the present disclosure contains the component (A) as an essential component, but various other components can be blended depending on the purpose. Other components include a radical polymerization initiator (B), an organic solvent (C), a reactive diluent (D), an antioxidant (E), an ultraviolet absorber (F), a pigment or dye (G), a silane coupling agent (H), and a surface modifier (I). These components will be described below. As for the other components described later, only one of the exemplified compounds may be used, or two or more of them may be used. may be used in combination.

[0042] 1) Radical polymerization initiator (B) The composition of the present disclosure may contain a photopolymerization initiator (B1) and / or a thermal polymerization initiator (B2) as the radical polymerization initiator (B).

[0043] 1-1) Photopolymerization initiator (B1) The composition of the present disclosure is used as an active energy ray curable composition, and further as an electron beam curable composition. When used as a composition, it is also possible to cure the composition by electron beam irradiation without containing the component (B1). When the composition of the present disclosure is used as an active energy ray-curable composition, it is preferable that the composition further contains a (B1) component, from the viewpoint of obtaining a composition having excellent curability, particularly when ultraviolet light and visible light are used as the active energy rays. When electron beams are used as the active energy rays, it is not necessarily required to add the active energy rays, but a small amount of the active energy rays can be added as necessary to improve the curability.

[0044] Specific examples of the component (B1) include benzil dimethyl ketal, benzil, benzoin, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, oligo[2-hydroxy-2-methyl-1-[4-1-(methylvinyl)phenyl]propanone, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl-propanone], 1-hydroxycyclohexyl phenyl ketone ... aromatic ketone compounds such as 2-methyl-1-[4-(methylthio)]phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)butan-1-one, 3,6-bis(2-methyl-2-morpholinopropionyl)-9-n-octylcarbazole, methyl phenylglyoxylate, ethyl anthraquinone and phenanthrenequinone; Benzophenone-based compounds such as benzophenone, 2-methylbenzophenone, 3-methylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, 4-phenylbenzophenone, 4-(methylphenylthio)phenylphenylmethane, methyl-2-benzophenone, 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-(4-methylphenylsulfonyl)propan-1-one, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone and 4-methoxy-4'-dimethylaminobenzophenone; acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphineate and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; Examples of thioxanthone compounds include thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 1-chloro-4-propylthioxanthone, 3-[3,4-dimethyl-9-oxo-9H-thioxanthone-2-yl-oxy]-2-hydroxypropyl-N,N,N-trimethylammonium chloride, and fluorothioxanthone.

[0045] Among these compounds, α-hydroxyphenyl ketones are preferred because they have good surface curing properties even in the form of a thin coating under atmospheric conditions. Specifically, 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-2-methyl-1-phenyl-propan-1-one are more preferred. In addition, when it is necessary to increase the thickness of the cured film, for example, when it is necessary to make it 50 μm or more, for the purpose of improving the curability inside the cured film, or when an ultraviolet absorber or pigment is used in combination, it is preferable to use acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, ethyl-(2,4,6-trimethylbenzoyl)phenyl phosphonate and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, 2-methyl-1-[4-(methylthio)]phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, etc. in combination.

[0046] The content of the (B1) component is preferably 0.01 to 15 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the total amount of the curable components. By making the content of the (B) component 0.01 parts by mass or more, the photocurability of the composition can be improved and the composition can have excellent adhesion, and by making the content 15 parts by mass or less, the internal curability of the cured film can be improved and the adhesion to the substrate can be improved. In addition, two or more types of initiators may be used in combination depending on the light source and film thickness used.

[0047] 1-2) Thermal polymerization initiator (B2) When the composition is used as a thermosetting composition, a thermal polymerization initiator (B2) can be added. The composition of the present disclosure can also be blended with component (B2) and cured by heating. As the component (B2), various compounds can be used, with organic peroxides and azo-based initiators being preferred.

[0048] Specific examples of organic peroxides include 1,1-bis(t-butylperoxy)2-methylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(4,4-di-butylperoxycyclohexyl)propane, 1, 1-bis(t-butylperoxy)cyclododecane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, -butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5-dimethyl-2,5-di(m-toluoylperoxy)hexane, t-butylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-hexylperoxybenzoate , 2,5-di-methyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxyacetate, 2,2-bis(t-butylperoxy)butane, t-butyl peroxybenzoate, n-butyl-4,4-bis(t-butylperoxy)valerate, di-t-butylperoxyisophthalate, α,α'-bis(t-butylperoxy)diisopropylbenzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane , t-butylcumyl peroxide, di-t-butyl peroxide, p-menthane hydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, diisopropylbenzene hydroperoxide, t-butyltrimethylsilyl peroxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, t-hexyl hydroperoxide, and t-butyl hydroperoxide. Specific examples of azo compounds include 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, azodi-t-octane, and azodi-t-butane. These may be used alone or in combination of two or more. It is also possible to carry out a redox reaction by combining with an agent.

[0049] The reducing agent used in the redox reaction includes an amine compound. The amine compound includes an alkylaniline. The alkylaniline reacts with an organic peroxide to generate an amine radical cation and a peroxide radical.

[0050] Specific examples of alkylanilines include N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-para-toluidine, N,N-diisopropyl-para-toluidine, N,N-dihydroxyethyl-para-toluidine, ethoxylated dihydroxyethyl-para-toluidine, and the like.

[0051] The content of the (B2) component is preferably 0.01 to 15 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the total amount of the curable components. By setting the content of the (B2) component to 0.01 parts by mass or more and 15 parts by mass or less, the thermosetting property of the composition can be improved and the adhesiveness can be improved. When the thermal polymerization initiator is used alone, it may be carried out according to a conventional method of normal radical thermal polymerization, and in some cases, it may be used in combination with a photopolymerization initiator, and after photocuring, thermal curing may be carried out in order to further improve the reaction rate. The content of the thermal polymerization initiator in the redox reaction refers to the content of the organic peroxide. In addition, as a method for producing a cured coating film by thermal polymerization, the composition is applied to a substrate, and when an organic solvent is contained, it is dried, and then the composition is placed in a vacuum dryer to reduce the pressure, or the oxygen concentration is sufficiently reduced under normal pressure with nitrogen flow, and then the composition is heated at preferably 60 to 100°C, more preferably 70 to 90°C, for 5 to 10 minutes. If the temperature is higher than 100°C, the substrate may deform if it is a heat-sensitive plastic film, or the substrate may deform due to thermal shrinkage during the process of lowering the temperature from the curing temperature to room temperature. On the other hand, if the temperature is lower than 60°C, it may take too long to obtain a cured coating film, which may cause problems in productivity.

[0052] 2) Organic solvents (C) The composition of the present disclosure may contain an organic solvent (C) component for the purpose of improving the coatability onto a substrate.

[0053] Specific examples of component (C) include alcohol compounds such as methanol, ethanol, isopropanol, and butanol; alkylene glycol monoether compounds such as ethylene glycol monomethyl ether and propylene glycol monomethyl ether; acetone alcohols such as diacetone alcohol; aromatic compounds such as benzene, toluene, and xylene; ester compounds such as propylene glycol monomethyl ether acetate, ethyl acetate, and butyl acetate; ketone compounds such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ether compounds such as dibutyl ether; and N-methylpyrrolidone. Among these, alkylene glycol monoether compounds and ketone compounds are preferred, and alkylene glycol monoether compounds are more preferred.

[0054] The content of the component (C) is preferably 10 to 1,000 parts by mass, more preferably 50 to 500 parts by mass, and even more preferably 50 to 300 parts by mass, relative to 100 parts by mass of the total amount of the curable components. When the content is within the above range, the composition can have a viscosity suitable for coating, and the composition can be easily coated by a known coating method described below.

[0055] 3) Reactive diluent (D) The composition of the present disclosure may contain a reactive diluent (D) component for the purpose of improving the coatability and adhesion to the substrate.

[0056] Component (D) is an ethylenically unsaturated compound (excluding component (A)), which is a component that is cured by heat or active energy rays. Component (C) needs to be removed by a drying process, which requires a large amount of thermal energy. Furthermore, when thermal energy is generated, a large amount of carbon dioxide is discharged, which places a very high burden on the environment. For this reason, the use of component (D) is preferred. Examples of "ethylenically unsaturated groups" include (meth)acryloyl groups, (meth)acrylamide groups, vinyl groups, and (meth)allyl groups, with (meth)acryloyl groups being preferred because they have good reactivity as ethylenically unsaturated groups.

[0057] In the component (D), examples of monofunctional (meth)acrylates include (meth)acrylic acid, Michael addition type dimer of acrylic acid, ω-carboxy-polycaprolactone mono(meth)acrylate, monohydroxyethyl phthalate (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, butyl carbitol (meth)acrylate, 2-ethylhexyl carbitol (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, (meth)acrylate of alkylene oxide adduct of phenol, (meth)acrylate of alkylene oxide adduct of alkylphenol, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, butyl carbitol (meth)acrylate, 2-ethylhexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, butyl carbitol (meth)acrylate, 2-ethylhexyl carbitol (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, (meth)acrylate of alkylene oxide adduct of phenol, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, butyl carbitol (meth)acrylate, 2-ethylhexyl ... Meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl acrylate, (meth)acrylate of alkylene oxide adduct of paracumylphenol, orthophenylphenol (meth)acrylate, (meth)acrylate of alkylene oxide adduct of orthophenylphenol, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecane methylol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerin mono(meth)acrylate, mono(meth)acrylate of alkylene oxide adduct of isocyanuric acid, N-(2-(meth)acryloxyethyl)hexahydrophthalimide, N-(2-(meth)acryloxyethyl)tetrahydrophthalimide, N,N-dimethylacrylamide, acryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, and the like. Examples of the alkylene oxide adduct include an ethylene oxide adduct, a propylene oxide adduct, and an ethylene oxide and propylene oxide adduct.Furthermore, the (D) component can be selected according to the purpose. For example, alkylene oxide-based acrylates can be used to reduce viscosity, tetrahydrofurfuryl acrylates can be used to improve adhesion, and acrylates having a hydroxyl group such as 4-hydroxybutyl acrylate can be used to improve curing properties.

[0058] Examples of bifunctional (meth)acrylate compounds include polyethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, glycerin di(meth)acrylate, di(meth)acrylate of an alkylene oxide adduct of isocyanuric acid, di(meth)acrylate of an alkylene oxide adduct of bisphenol A, di(meth)acrylate of an alkylene oxide adduct of bisphenol F, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, and nonanediol di(meth)acrylate. In addition, epoxy (meth)acrylates having a bisphenol skeleton, a polyether skeleton, or a polyalkylene skeleton, urethane (meth)acrylates having a polyester skeleton, a polyether skeleton, or a polycarbonate skeleton, and polyester (meth)acrylates can also be used.

[0059] Examples of polyfunctional (meth)acrylate compounds include polyol poly(meth)acrylates such as glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri- or tetra(meth)acrylate, ditrimethylolpropane tri- or tetra(meth)acrylate, and dipentaerythritol tri-, tetra-, penta- or hexa(meth)acrylate; Poly(meth)acrylates of polyol alkylene oxide adducts such as tri- or tetra(meth)acrylates of pentaerythritol alkylene oxide adducts, tri- or tetra(meth)acrylates of ditrimethylolpropane alkylene oxide adducts, and tri-, tetra-, penta-, or hexa(meth)acrylates of dipentaerythritol alkylene oxide adducts; Examples of the alkylene oxide adduct include tri(meth)acrylate of isocyanuric acid alkylene oxide adduct; and urethane (meth)acrylate, which is a reaction product of a compound having a hydroxyl group and three or more (meth)acryloyl groups, such as pentaerythritol tri(meth)acrylate, with an organic polyisocyanate. Examples of the alkylene oxide adduct include an ethylene oxide adduct, a propylene oxide adduct, and an ethylene oxide and propylene oxide adduct.

[0060] The content of component (D) is 1 to 99% by mass, more preferably 5 to 40% by mass, and even more preferably 7 to 15% by mass, based on 100 parts by mass of the total amount of components (A) and (D). When the content of component (D) is 1% by mass or more, the composition does not become too viscous, resulting in good coatability and adhesion, and when it is 99% by mass or less, the coating film strength of the curable composition is good.

[0061] 4) Antioxidants (E) Component (E) is added for the purpose of improving the durability, such as heat resistance and weather resistance, of the cured film. Examples of the component (E) include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants.

[0062] Examples of the phenol-based antioxidant include hindered phenols such as di-t-butylhydroxytoluene. Commercially available antioxidants include AO-20, AO-30, AO-40, AO-50, AO-60, AO-70, and AO-80 manufactured by Adeka Corporation. Examples of phosphorus-based antioxidants include phosphines such as trialkylphosphine and triarylphosphine, trialkyl phosphites, triaryl phosphites, etc. Commercially available derivatives of these include Adeka STAB PEP-4C, PEP-8, PEP-24G, PEP-36, HP-10, 260, 522A, 329K, 1178, 1500, 135A, and 3010, manufactured by Adeka Corporation. Examples of the sulfur-based antioxidant include thioether-based compounds, and examples of commercially available products include AO-23, AO-412S, and AO-503A manufactured by Adeka Corporation. These antioxidants may be used alone or in combination of two or more. Preferred combinations of these antioxidants include a combination of a phenol-based antioxidant and a phosphorus-based antioxidant, and a combination of a phenol-based antioxidant and a sulfur-based antioxidant.

[0063] The content of the component (E) may be appropriately set depending on the purpose, and is preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 1 part by mass, per 100 parts by mass of the total amount of the curable components. By setting the content ratio to 0.1 parts by mass or more, the durability of the composition can be improved, while by setting it to 5 parts by mass or less, the curability and adhesion can be improved.

[0064] 5) Ultraviolet absorber (F) The component (F) is added for the purpose of improving the light resistance of the cured film. Examples of the component (F) include triazine-based ultraviolet absorbers such as TINUVIN 400, TINUVIN 405, TINUVIN 460, and TINUVIN 479, and benzotriazole-based ultraviolet absorbers such as TINUVIN 900, TINUVIN 928, and TINUVIN 1130, both manufactured by BASF.

[0065] The content of component (F) may be appropriately set depending on the purpose, and is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the total amount of the curable components. By setting the content to 0.01% by mass or more, the light resistance of the cured film can be made good, while by setting it to 5% by mass or less, the curability of the composition can be made excellent.

[0066] 6) Pigments and dyes (G) Examples of the pigment include organic pigments and inorganic pigments. Specific examples of organic pigments include insoluble azo pigments such as toluidine red, toluidine maroon, Hansa yellow, benzidine yellow, and pyrazolone red; soluble azo pigments such as lithol red, heliobordeaux, pigment scarlet, and permanent red 2B; derivatives of vat dyes such as alizarin, indanthrone, and thioindigo maroon; phthalocyanine organic pigments such as phthalocyanine blue and phthalocyanine green; quinacridone organic pigments such as quinacridone red and quinacridone magenta; perylene organic pigments such as perylene red and perylene scarlet; and isoindigo. isoindolinone organic pigments such as perinone yellow and isoindolinone orange; pyranthrone organic pigments such as pyranthrone red and pyranthrone orange; thioindigo organic pigments; condensed azo organic pigments; benzimidazolone organic pigments; quinophthalone organic pigments such as quinophthalone yellow, isoindoline organic pigments such as isoindoline yellow, and other pigments such as flavanthrone yellow, acylamide yellow, nickel azo yellow, copper azomethine yellow, perinone orange, anthrone orange, dianthraquinonyl red, and dioxazine violet. Specific examples of the inorganic pigment include titanium oxide, barium sulfate, calcium carbonate, zinc oxide, lead sulfate, yellow lead, zinc yellow, red iron oxide (red iron (III) oxide), cadmium red, ultramarine, Prussian blue, chromium oxide green, cobalt green, umber, titanium black, and synthetic iron black. Carbon black, which is an example of the filler, can also be used as an inorganic pigment. As the dye, various conventionally known compounds can be used.

[0067] 7) Silane coupling agent (H) Component (H) is blended for the purpose of improving the interfacial adhesive strength between the cured film and the substrate. There are no particular limitations on the component (H) as long as it can contribute to improving the adhesiveness to the substrate.

[0068] Examples of the component (H) include (meth)acrylate compounds, amine compounds, and thiol compounds. Specific examples thereof include γ-methacryloxypropyltrimethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyltributoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-( Examples of the silane include N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropyltrimethoxysilane.

[0069] The blending ratio of the (H) component may be appropriately set depending on the purpose, and is preferably 0.1 to 10 parts by mass, and more preferably 1 to 5 parts by mass, per 100 parts by mass of the total amount of the curable components. By making the blending ratio 0.1 parts by mass or more, the adhesive strength of the composition can be improved, while by making it 10 parts by mass or less, the change in adhesive strength over time can be prevented.

[0070] 8) Surface modifiers (I) Component (I) may be added to the composition of the present disclosure for the purposes of improving the leveling properties during application and increasing the slip properties of the cured film to improve scratch resistance. Examples of the component (I) include surface conditioners, surfactants, leveling agents, defoamers, agents for imparting smoothness, agents for imparting antifouling properties, etc., and these known surface modifiers can be used. Among them, silicone-based surface modifiers and fluorine-based surface modifiers are preferred.Specific examples include silicone-based polymers and oligomers having a silicone chain and a polyalkylene oxide chain, silicone-based polymers and oligomers having a silicone chain and a polyester chain, fluorine-based polymers and oligomers having a perfluoroalkyl group and a polyalkylene oxide chain, and fluorine-based polymers and oligomers having a perfluoroalkyl ether chain and a polyalkylene oxide chain. For the purpose of improving the durability of the lubrication property, a surface modifier having an ethylenically unsaturated group, preferably a (meth)acryloyl group, in the molecule may be used.

[0071] The content of component (I) is preferably 0.01 to 1.0 part by mass per 100 parts by mass of the total amount of the curable components. Within this range, the coating film will have excellent surface smoothness.

[0072] The composition of the present disclosure has a gel fraction of 95% or more as measured by the following measurement method. The gel fraction is preferably 96% or more, more preferably 97% or more, even more preferably 99% or more, and particularly preferably 100%. By having a gel fraction of the above lower limit or more, the solvent resistance of the cured film is improved, and it is possible to achieve both hardness and flexibility. (Method of Measuring Gel Fraction) A composition containing 0.1 to 10 parts by mass of a photopolymerization initiator per 100 parts by mass of a component having an ethylenically unsaturated bond is applied to a film thickness of 10 μm, and then exposed to UV-A intensity of 250 mW / cm using a light source such as a high-pressure mercury lamp, a metal halide lamp, or a UV-LED. 2 , 200mJ / cm 2The active energy ray is irradiated with an integrated light amount of 10 ... Gel fraction = C2 / C1 × 100 (X) C1: Mass of the cured film before immersion in ethyl acetate C2: Mass of the cured film after immersion in ethyl acetate

[0073] The composition of the present disclosure may be used in a conventional manner. For example, a method in which the composition is applied to a substrate and then cured by irradiating with active energy rays or by heating can be mentioned. Specifically, in the case of applications such as coating agents and adhesives, the composition is applied to a substrate by a normal coating method, and then, in the case of an active energy ray-curable composition, the composition is cured by irradiation with active energy rays, or in the case of a thermosetting composition, the composition is cured by heating, etc. In the case of applications such as molding materials, the composition is injected into a predetermined mold, and then, in the case of an active energy ray-curable composition, the composition is cured by irradiation with active energy rays, or in the case of a thermosetting composition, the composition is cured by heating, etc. The method of irradiating with active energy rays and the method of heating may be any common method known as a conventional curing method. In addition, a method can also be employed in which the composition contains a component (B1) (photopolymerization initiator) and a component (B2) (thermal polymerization initiator) in combination, which is then irradiated with active energy rays and then cured by heating to improve adhesion to the substrate.

[0074] The composition of the present disclosure can be applied to a variety of substrates, including plastics, wood, metals, inorganic materials, and paper. Specific examples of plastics include polyvinyl alcohol, cellulose acetate resins such as triacetyl cellulose and diacetyl cellulose, acrylic resins, polyethylene terephthalate, polycarbonate, polyarylate, polyethersulfone, cyclic polyolefin resins having cyclic olefins as monomers such as norbornene, polyvinyl chloride, epoxy resins, and polyurethane resins. Wood includes natural wood and synthetic wood. Examples of metals include steel sheets, metals such as aluminum and chromium, and metal oxides such as zinc oxide (ZnO) and indium tin oxide (ITO). Inorganic materials include glass, mortar, concrete, and stone. The curable composition obtained by the present disclosure has excellent hardness, and therefore can impart scratch resistance to substrates whose surfaces are easily scratched, and can provide a coating member that follows the deformation of the substrate, so plastic substrates are particularly preferred.

[0075] The thickness of the cured film of the composition on the substrate may be appropriately set depending on the purpose. The thickness of the cured film may be selected depending on the substrate to be used and the application of the substrate having the produced cured film, but is preferably 1 to 500 μm, more preferably 5 to 200 μm.

[0076] The method for applying the composition of the present disclosure to a substrate may be appropriately selected depending on the purpose. Coater, applicator, doctor blade, dip coater, roll coater, Pin coater, flow coater, knife coater, comma coater, reverse roll coater coater, die coater, lip coater, gravure coater and micro gravure coater and the like.

[0077] Examples of active energy rays for curing the composition of the present disclosure include ultraviolet rays, visible light, and electron beams, with ultraviolet rays being preferred. Examples of ultraviolet irradiation devices include high-pressure mercury lamps, metal halide lamps, ultraviolet (UV) electrodeless lamps, and light-emitting diodes (LEDs). The irradiation energy should be set appropriately depending on the type of active energy ray and the compounding composition. For example, when using a high-pressure mercury lamp, the irradiation energy in the UV-A region is 10 to 10,000 mJ / cm. 2 is preferable, and 100 to 2,000 mJ / cm 2 is more preferred.

[0078] 3.Applications The composition of the present disclosure can be used for various applications, specifically, for applications such as inks, coating agents, and adhesives.

[0079] The composition of the present disclosure can be preferably used as an active energy ray-curable composition, and since it has excellent curability and the cured film has excellent hardness and flexibility, it can be more preferably used as a coating agent. EXAMPLES

[0080] The present disclosure will be described more specifically below with reference to examples and comparative examples.

[0081] 1. Manufacturing Example 1) Manufacturing Example 1 Into a 1 L flask equipped with a stirrer, a thermometer, and a piping for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON), 497.99 g of glycerin acrylate (a2) [manufactured by Toagosei Co., Ltd., trade name: Aronix M-920, acrylic equivalent: 103 g / eq], 0.35 g of 2,6-di-t-butyl-4-methylphenol (hereinafter referred to as BHT), and 0.14 g of dibutyltin dilaurate (hereinafter referred to as DBTDL) were charged. The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. Pentamethylene diisocyanate (trade name: STABIO PDI, manufactured by Mitsui Chemicals, Inc., hereinafter referred to as PDI) was gradually added as organic polyisocyanate (a1). Finally, 148.98 g of PDI was charged. After that, the temperature inside the flask was raised to 80°C. Thereafter, the amount of remaining isocyanate groups was measured by infrared absorption spectrometry (hereinafter referred to as IR measurement) [μ-ATR method] using Spectrum 100 manufactured by PerkinElmer Japan Co., Ltd., and the synthesis was terminated when it was confirmed that the isocyanate groups had disappeared. The reaction product obtained was mainly composed of tetrafunctional urethane acrylate (area ratio measured by gel permeation chromatography (hereinafter referred to as GPC) was 82%, hereinafter referred to as "A-1"). The proportion of urethane acrylate in component (A) is preferably 70% or more in area ratio measured by GPC. When the area ratio is higher than 70%, the hardness and flexibility are excellent, and when it is lower than 70%, the flexibility is deteriorated.

[0082] The acrylic equivalent and GPC were measured according to the following methods.

[0083] Acrylic equivalent measurement conditions Calculated from the bromine number measured in accordance with JIS K2605-1996.

[0084] GPC measurement conditions Apparatus: Waters GPC system name 15152414717PRI Detector: RI detector Column: Guard column: Showa Denko Co., Ltd., Shodex KFG (8 μm 4.6 × 10 mm), main column: Waters Co., Ltd., 2 types of styragel HR4ETHF (7.8 × 300 mm) + styragel HR1THF (7.8 × 300 mm) Column temperature: 40℃ Eluent composition: THF (containing 0.03% sulfur as an internal standard), flow rate 0.75 mL / min

[0085] 2) Manufacturing Example 2 Into a 1 L flask equipped with a stirrer, a thermometer, and a pipe for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON), 498.03 g of Aronix M-920, 0.39 g of BHT, and 0.17 g of DBTDL were charged as (meth)acrylate (a2). The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. PDI isocyanurate (manufactured by Mitsui Chemicals, Inc., product name: STABIO D-376N) was gradually added as organic polyisocyanate (a1). Finally, 294.54 g of PDI isocyanurate was charged. Then, the temperature inside the flask was raised to 80°C. The disappearance of the isocyanate groups was confirmed by subsequent IR measurement, and the synthesis was terminated. The obtained reaction product was mainly composed of a hexafunctional urethane acrylate (area ratio measured by GPC was 84%, hereinafter referred to as "A-2").

[0086] 3) Manufacturing Example 3 Into a 1 L flask equipped with a stirrer, a thermometer, and a piping for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON), 486.95 g of pentaerythritol acrylate (a2) (manufactured by Toagosei Co., Ltd., trade name: ARONIX M-934, acrylic equivalent: 100 g / eq), 0.37 g of BHT, and 0.18 g of DBTDL were charged. The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. PDI was gradually added as the organic polyisocyanate (a1) until 148.98 g of PDI was finally charged. Thereafter, the temperature inside the flask was raised to 80°C. The disappearance of the isocyanate groups was confirmed by subsequent IR measurement, and the synthesis was terminated. The reaction obtained was found to be mainly composed of hexafunctional urethane acrylate (area ratio measured by GPC was 85%, hereinafter referred to as "A-3").

[0087] 4) Manufacturing Example 4 A 1 L flask equipped with a stirrer, a thermometer, and a pipe for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON) was charged with 43.23 g of 1,4-butanediol (manufactured by Mitsubishi Chemical Corporation under the trade name of 14BG), 249.92 g of M-920, 0.28 g of BHT, and 0.14 g of DBTDL. The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. PDI was gradually added as the organic polyisocyanate (a1) until 147.85 g of PDI was finally charged. Thereafter, the temperature inside the flask was raised to 80°C. The disappearance of the isocyanate groups was confirmed by subsequent IR measurement, and the synthesis was terminated. The obtained reaction product was mainly composed of tetrafunctional urethane acrylate (area ratio measured by GPC was 84%, hereinafter referred to as "A-4").

[0088] 5) Manufacturing Example 5 Into a 1 L flask equipped with a stirrer, a thermometer, and a pipe for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON), 498.87 g of Aronix M-920, 0.36 g of BHT, and 0.13 g of DBTDL were charged as (meth)acrylate (a2). The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. Hexamethylene diisocyanate (Duranate 50M-HDI, Asahi Kasei Corporation, hereinafter referred to as HDI) was gradually added. Finally, 163.88 g of HDI was charged. Then, the temperature inside the flask was raised to 80°C. The disappearance of the isocyanate groups was confirmed by subsequent IR measurement, and the synthesis was terminated. The obtained reaction product was mainly composed of tetrafunctional urethane acrylate (area ratio measured by GPC was 82%, hereinafter referred to as "A-5").

[0089] 6) Manufacturing Example 6 Into a 1 L flask equipped with a stirrer, a thermometer, and a pipe for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON), 498.55 g of Aronix M-920, 0.34 g of BHT, and 0.16 g of DBTDL were charged as (meth)acrylate (a2). The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. HDI isocyanurate (Duranate TPA200, Asahi Kasei Corporation; hereinafter referred to as HDI isocyanurate) was gradually added. Finally, 322.51 g of HDI isocyanurate was charged. Then, the temperature inside the flask was raised to 80°C. The disappearance of the isocyanate groups was confirmed by subsequent IR measurement, and the synthesis was terminated. The obtained reaction product was mainly composed of a hexafunctional urethane acrylate (area ratio measured by GPC was 84%, hereinafter referred to as "A-6").

[0090] 7) Manufacturing Example 7 In a 1 L flask equipped with a stirrer, a thermometer, and a pipe for an oxygen / nitrogen mixed gas with an oxygen concentration of 5% (hereinafter referred to as 5% ON), 499.79 g of 4-HBA, 0.43 g of BHT, and 0.27 g of DBTDL were charged as (meth)acrylate (a2). The contents were stirred while blowing in 5% ON, and the temperature inside the flask was raised to 70°C. HDI was gradually added. Finally, 277.71 g of HDI was added. Then, the temperature inside the flask was raised to 80°C. The disappearance of the isocyanate groups was confirmed by subsequent IR measurement, and the synthesis was terminated. The obtained reaction product was mainly composed of a bifunctional urethane acrylate (area ratio measured by GPC was 93%, hereinafter referred to as "A-7").

[0091] The materials used in the above Production Examples 1 to 7 (A-1 to A-7) are shown in Table 1.

[0092] [Table 1]

[0093] 2. Examples and Comparative Examples 1) Production of active energy ray-curable composition The compounds shown in Table 2 below were stirred and mixed in the ratios shown in Table 2 to prepare active energy ray-curable compositions. The obtained composition was used to carry out the evaluations described below, and the results are shown in Table 2.

[0094] 2) Evaluation method for cured film ◆ Manufacturing of hardened films The composition obtained in Table 2 was applied to a polyethylene terephthalate film (Toyobo Co., Ltd., Cosmoshine (registered trademark) 4360 (thickness 100 μm), hereinafter referred to as "PET") having a width of 300 mm and a length of 300 mm, with an applicator to form a coating film having a thickness of 10 μm. After this, a high-pressure mercury lamp manufactured by Eye Graphics Co., Ltd. was used, and the ultraviolet region (UV-A) intensity was set at 365 nm and 250 mW / cm 2 200mJ / cm per pass 2 The coating was conveyed in an air atmosphere using a conveyor adjusted to provide an irradiation energy of 1000 nm, and was irradiated with ultraviolet light in one pass to obtain a cured coating film.

[0095] (1) Acryloyl group reaction rate The reaction rate of the acryloyl group in the cured film was calculated from IR measurement by the μ-ATR method. Using the obtained infrared absorption spectrum, the reaction rate of the acryloyl group was calculated according to the following formula (1). Acryloyl group reaction rate = {1 - (B2 / A2) / (B1 / A1)} × 100 (1) A1: 1724 cm due to -C=O of the composition -1 Peak height of B1: 1405 cm due to -CH=CH2 of the composition -1 Peak height of A2: 1724 cm originating from -C=O of the cured film -1 Peak height of B2: 1405 cm originating from -CH=CH2 of the cured film -1 Peak height of The closer this value is to 100%, the more the unsaturated double bonds that contribute to the polymerization reaction have disappeared, and the more excellent the curability of the composition is.

[0096] (2) Pencil hardness The pencil hardness of the resulting cured film was measured under a load of 750 g in accordance with JIS K 5600-5-4.

[0097] (3) Flexibility According to the mandrel test (JIS K 5600-5-1), the PET film on which the cured coating was formed was wrapped around a core rod having a diameter of 2 mm to 10 mm, and the smallest core rod diameter at which no cracks or peeling were observed was evaluated.

[0098] (4) Rubbing test The surface of the cured film was rubbed with a cotton swab soaked in acetone, and the occurrence of abnormal appearance such as whitening or peeling on the surface of the cured film was qualitatively evaluated on the following three-point scale. 〇: No abnormality in the appearance of the cured film even after rubbing 20 times or more △: Abnormalities in the appearance of the cured film occurred after rubbing 5 to 20 times. ×: Abnormalities in the appearance of the cured film occurred after rubbing less than 5 times

[0099] (5) Viscoelasticity spectrum Using a viscoelasticity measuring device DMA850 manufactured by TA Instruments, measurements were performed in tension mode at a frequency of 1 Hz and a heating rate of 2° C. / min, and the storage modulus E' (GPa) at 40° C. was recorded.

[0100] (6) Tensile properties Using an Instron 5566A, the tensile strength (MPa) at break was measured under conditions of a jig distance of 20 mm, a tensile speed of 10 mm / min, and a temperature of 40°C.

[0101] (7) Gel fraction The cured film was weighed to three decimal places, approximately 5 g, and 50 g of ethyl acetate. The above-mentioned cured film was immersed in ethyl acetate and left to stand for 24 hours in a 25°C environment. After standing, the cured film immersed in ethyl acetate was filtered using a 200-mesh filter cloth. The cured film was thoroughly washed with ethyl acetate and thoroughly dried until no ethyl acetate remained in the cured film. After drying, the mass of the cured film was precisely weighed, and the gel fraction (%) was calculated using the following formula (2). Gel fraction = C2 / C1 × 100 (2) C1: Mass of the cured film before immersion in ethyl acetate C2: Mass of the cured film after immersion in ethyl acetate The closer this value is to 100%, the better the solvent resistance is, and the greater the hardness is without impairing flexibility.

[0102] [Table 2]

[0103] In Table 2, parts means parts by mass, and the abbreviations have the following meanings. HCPK: 1-Hydroxycyclohexyl phenyl ketone, Omnirad 184 from IGMRESINS M-113: Nonylphenol EO modified (n=4) acrylate, Toagosei "Aronix M-113"

[0104] As is clear from the results of Examples 1 to 5, the composition of the present disclosure has excellent curability even under conditions of low irradiation dose of active energy rays, and when used as a cured coating film, it has excellent hardness, flexibility, rubbing test, storage modulus, and tensile strength at break. Therefore, from the viewpoint of energy consumption, it is possible to reduce the environmental load and improve the productivity of the cured coating film. In contrast, the compositions of Comparative Examples 1 to 3 and 5 were compositions made of aliphatic isocyanates that did not contain pentamethylene group components, but they had poor curability, and when used as cured coating films, the hardness and flexibility were deteriorated due to the influence of the remaining unreacted monomer. Furthermore, in the composition of Comparative Example 4, component (A) is a (meth)acrylate obtained by reacting one type of alcohol selected from the group consisting of polyhydric alcohols having two hydroxyl groups with a compound having one (meth)acryloyl group, so the curability was poor, and when used as a cured coating film, the hardness and tensile strength at break were deteriorated due to the influence of the remaining unreacted monomer and the degree of crosslinking. [Industrial Applicability]

[0105] The composition of the present disclosure relates to a curable composition, and can be preferably used as an active energy ray curable composition in particular. Furthermore, the specific applications of the composition of the present disclosure include inks, coating agents, adhesives, and the like.

Claims

1. A curable composition comprising the following component (A): Component (A): a reaction product of an organic polyisocyanate (a1) having an odd number of methylene group structures and at least one (meth)acrylate (a2) having one or more hydroxyl groups and an acrylic equivalent of 50 to 200 g / eq.

2. The curable composition according to claim 1 , wherein the organic polyisocyanate (a1) is a polyisocyanate having a pentamethylene group.

3. The curable composition according to claim 1, wherein the (meth)acrylate (a2) is a (meth)acrylate obtained by reacting one alcohol selected from the group consisting of polyhydric alcohols having 3 to 6 hydroxyl groups with a compound having one (meth)acryloyl group.

4. The curable composition according to claim 1 , which is an active energy ray curable composition.

5. The composition contains 0.1 to 10 parts by mass of a photopolymerization initiator for 100 parts by mass of a component having an ethylenically unsaturated bond, is coated to a thickness of 10 μm, and has a UV-A intensity of 250 mW / cm 2 , 200 mJ / cm 2 2. The curable composition according to claim 1, wherein the gel fraction calculated from the mass (C1) of a cured film obtained by irradiating active energy rays with an integrated light amount of 1000 nm to 2000 nm and the mass (C2) of the cured film obtained by immersing the cured film in ethyl acetate, leaving it at rest in a 25° C. environment for 24 hours, filtering it using a 200-mesh filter cloth, and drying it is 95% or more by the following formula (X): Gel fraction = C2 / C1 × 100 ... (X) C1: Mass of the cured film before immersion in ethyl acetate C2: Mass of the cured film after immersion in ethyl acetate

6. The curable composition according to claim 5 , wherein the component (A) accounts for 60 mass % or more of the ethylenically unsaturated bond-containing component (100 mass %).

7. The curable composition according to any one of claims 1 to 6, which is used as a coating agent.

Citation Information

Patent Citations

  • Actinic radiation curable compositions containing semiconducting metal oxide materials

    JP2022060346A

  • Active energy ray-curable type resin composition and cured product of the same

    JP2023049953A

Cited By

  • Method of processing substrate, method of manufacturing semiconductor device, program, and substrate processing apparatus

    EP4788111A1